Walnut shell activated carbon: optimization of synthesis process, characterization and application for Zn (II) removal in batch and continuous process. (24th May 2019) - Davidi, Shahla; Lashanizadegan, Asghar; Sharififard, Hakimeh
Abstract: The walnut shell, as local agriculture biomass of Yasouj city (Iran), was used as raw material to synthesize activated carbon. The optimum condition of the synthesis process was determined using Taguchi experimental design and the adsorption abilities of the produced activated carbon toward Zn (II) was used as response. The analysis of data showed that the impregnation ratio and activation time are more effective parameters. The activated carbon synthesized at optimum condition was a mesopore material with the specific surface area of 1388 m 2 g −1 . The optimum activated carbon was applied as the adsorbent for Zn (II) removal from aqueous solution under the different operating condition including initial pH, contact time and initial concentration. The kinetics analysis of data indicates the chemical nature of Zn ions adsorption. The produced carbon was able to adsorb 89 mg Zn (II) per each gram. The adsorption ability of produced carbon was evaluated in three adsorption/desorption cycles in a continuous adsorption system.